2018
DOI: 10.1515/aot-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Residual heat generated during laser processing of CFRP with picosecond laser pulses

Abstract: One of the major reasons for the formation of a heat-affected zone during laser processing of carbon fiber-reinforced plastics (CFRP) with repetitive picosecond (ps) laser pulses is heat accumulation. A fraction of every laser pulse is left as what we termed residual heat in the material also after the completed ablation process and leads to a gradual temperature increase in the processed workpiece. If the time between two consecutive pulses is too short to allow for a sufficient cooling of the material in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Laser ablation of materials in a medium is a complex physical process that depends on the parameters of laser radiation, the properties of the working medium, and additional sources of physical impact. An additional source of influence can be both the thermal load caused by the action of the laser-induced plasma torch [1], which is formed above the treated surface, and the energy applied to the treatment area together with the laser beam [2][3][4][5]. The combination of various methods of exposure allows achieving a synergistic effect, and, as a consequence, increasing the efficiency of the ablation operation.…”
Section: Introductionmentioning
confidence: 99%
“…Laser ablation of materials in a medium is a complex physical process that depends on the parameters of laser radiation, the properties of the working medium, and additional sources of physical impact. An additional source of influence can be both the thermal load caused by the action of the laser-induced plasma torch [1], which is formed above the treated surface, and the energy applied to the treatment area together with the laser beam [2][3][4][5]. The combination of various methods of exposure allows achieving a synergistic effect, and, as a consequence, increasing the efficiency of the ablation operation.…”
Section: Introductionmentioning
confidence: 99%
“…Völkermeyer et al 4 discussed the influence of filling distance and cycle times on ablation depth and ablation amount and proved that the maximum value of material strength decreased significantly in the total processing time. Christian et al 5 studied the relationship between the residual heat in CFRP and the volume of the laser beam, the pulse overlap, and the depth of the lasergenerated groove. The results showed that the residual heat gradually increased with the increase of the groove depth.…”
Section: Introductionmentioning
confidence: 99%